Pengaruh Penerapan Pelayanan Prima Terhadap Kepuasan Pasien Rawat Jalan di RSUD Labuang Baji Makassar - Pratiwi, Reski Dewi; Putra, Ryryn Suryaman Prana (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2021)
The number of outpatient visits at Labuang Baji Hospital, Makassar decreased from 2017 as many as 47.773 patients to 45.591 patients where the decrease in the number of outpatient visits was indicated to be related to the excellent service provided by the hospital. This study aims to analyze the effect of the application of excellent service on the satisfaction of outpatients at the Labuang Baji Hospital, Makassar. This type of research is a quantitative study using a cross sectional study design. This research was conducted in the outpatient room of the Labuang Baji Hospital, Makassar. The total sample was 397 outpatients. Data were collected using a questionnaire tool. Data were analyzed using the chi square test at α <5%. The results showed that there was an effect of excellent service from the Attitude with a value of p=0,007, Attention with a value of p=0,001, Action with a value of p=0,003, Ability with a value of p=0,001, Appearance with a value of p=0,000, and Accountability with a value of p=0,000 on outpatient satisfaction at Labuang Baji Hospital, Makassar. It is expected that the Labuang Baji Hospital, Makassar will pay attention and maintain the items of Attitude, Attention, Action, Ability, Appearance, and Accountability because it is scientifically proven affect to outpatient satisfaction.